Properties of wood cement board (WCB) made from Sentang (Azadirachta excelsa) particles / Iffah Izzah Maidin - Maidin, Iffah Izzah (2012)
The mechanical and physical properties of wood cement board from Sentang (Azadirachta excelsa) will determine based on the effect of wood particle sizes in wood cement board manufacturing. The quality of the boards were evaluated by determine the bending properties such as modulus of elasticity (MOE) and modulus of rupture (MOR), internal bonding (IB), screw withdrawal (SW), thickness swelling(TS) and water absorption (WA). The effects of different three particle sizes (0.5mm, 1.0mm and 2.0mm) were determined. All board properties were significantly influenced by particle sizes. Only wood cement board using wood particle size of 2.0mm meet the requirement for mechanical and physical properties as stipulated in MS standard (MS544: 2001)